Telomere maintenance in interplay with DNA repair in pathogenesis and treatment of colorectal cancer - Tomasova, Kristyna; Kroupa, Michal; Forsti, Asta; Vodicka, Pavel; Vodickova, Ludmila (Mutagenesis, 2020)
Colorectal cancer (CRC) continues to be one of the leading malignancies and causes of tumour-related deaths worldwide. Both impaired DNA repair mechanisms and disrupted telomere length homeostasis represent key culprits in CRC initiation, progression and prognosis. Mechanistically, altered DNA repair results in the accumulation of mutations in the genome and, ultimately, in genomic instability. DNA repair also determines the response to chemotherapeutics in CRC treatment, suggesting its utilisation in the prediction of therapy response and individual approach to patients. Telomere attrition resulting in replicative senescence, simultaneously by-passing cell cycle checkpoints, is a hallmark of malignant transformation of the cell. Telomerase is almost ubiquitous in advanced solid cancers, including CRC, and its expression is fundamental to cell immortalisation. Therefore, there is a persistent effort to develop therapeutics, which are telomerase-specific and gentle to non-malignant tissues. However, in practice, we are still at the level of clinical trials. The current state of knowledge and the route, which the research takes, gives us a positive perspective that the problem of molecular models of telomerase activation and telomere length stabilisation will finally be solved. We summarise the current literature herein, by pointing out the crosstalk between proteins involved in DNA repair and telomere length homeostasis in relation to CRC.
Keywords: kolorektální nádory; Colorectal Neoplasms; kontrolní body buněčného cyklu; Cellular Senescence; Telomere Homeostasis; Cell Cycle Checkpoints; homeostáza telomer; Humans; oprava DNA; telomerasa; Telomerase; chromozomální nestabilita; Telomere; nádorová transformace buněk; telomery; DNA Repair; Cell Transformation, Neoplastic; lidé; Chromosomal Instability; stárnutí buněk